“Watch and wait” approach in the treatment of advanced radioiodine refractory differentiated thyroid cancer: a study of barriers and drivers of use - E. V. Borodavina; A. Yu. Shurinov; S. I. Kutukova; E. N. Nedozorova; A. V. Malanchuk; Yu. V. Semenchenko; S. M. Povarkov; K. V. Narovenkova; A. V. Khodkevich; Yu. V. Komoza; K. A. Kofanova; S. P. Dmitriev; et al. (Опухоли головы и шеи)
Introduction. The multikinase inhibitors have demonstrated high clinical efficacy in treatment of the radioiodine refractory differentiated thyroid cancer. At the same time, the inclusion criteria in the studies has reflected a minimum set of characteristics important for beginning of use of these drugs and an approach that takes into account the tumor progression rate (the volume doubling time) in the absence of clinical manifestations of the disease that have made it possible to individualize the start of therapy.   Aim. To describe and evaluate the barriers and drivers of use the “watch and wait” approach by Russian oncologists in treatment of the radioiodine refractory thyroid cancer.   Materials and methods. We conducted 35 structured interviews with oncologists observing patients after radioiodine therapy in order to evaluate the “watch and wait” approach. unfortunately, data on use and prevalence of this approach in Russia are limited. The present study involved the use of deductive content analysis as well as analysis of implementation model of clinical guidelines and included investigation of issue of implementation of the “watch and wait” approach to current practice of therapy for radioiodine refractory differentiated thyroid cancer. One of the main tasks was to determine the influence of external factors on the treatment of this category of patients.   Conclusion. Barriers and drivers of using “watch and wait” approach in the treatment of differentiated radioiodine refractory thyroid cancer are identified at several levels. for wide use of this approach, it is necessary to involve oncologists taking into account their attitude regarding changes in routine practices, patient expectations and to obtain additional data regarding its long-term effectiveness.